Canadian annual review of politics and public affairs, 1987 - Byers, R. B. (Canadian Annual Review of Politics and Public Affairs., 1991)
The Canadian Annual Review has become an indispensable reference work for all concerned with Canadian public affairs. Complied by a corps of Canadian scholars and experts, it offers both a concise, convenient record of the year's events and an authoritatibve appraisal of developments.The present volume covers events in a watershed year. In constitutional matters 1987 saw the most important even since the passage of the Constitutional Act of 1982: the Meech Lake Accord.In the House of Commons, new drug patent legislation and a bill to control more tightly the influx of immigrants and refugees faced strenuous opposition. A proposal to reinstate capital punishment was rejected in a free vote.Overall the Canadian economy performed well, although slumping oil and gas prices continued to create problems in the western provinces, Ontario Premier David Peterson was re-elected, this time with an overwhelming Liberal majority. But the dominant story in Canadian newspapers throughout the year was free trade with the United States.